Agronomic Trait Variations and Ploidy Differentiation of Kiwiberries in Northwest China: Implication for Breeding - Zhang, Ying; Zhong, Caihong; Liu, Yifei; Zhang, Qiong; Sun, Xiaorong; Li, Dawei (Frontiers in Plant Science, 2017)
Polyploid plants often have higher biomass and superior crop qualities. Breeders therefore search for crop germplasm with higher ploidy levels; however, whether higher ploidy levels are associated with better performance remains unclear. Actinidia arguta and related species, whose commercialized fruit are referred to as kiwiberries, harbour a series of ploidy races in nature, offering an opportunity to determine the link between ploidy levels and agronomic traits. In the present study, we determined the ploidy levels of A. arguta var. arguta, A. arguta var. giraldii and A. melanandra in 16 natural populations using flow cytometry, and examined 31 trait variations in fruits, leaves and flowers by field observations, microscopic examination and laboratory analyses. Our results showed that octaploid and decaploid A. arguta var. giraldii had larger dimension of leaves than tetraploid A. arguta var. arguta and A. melanandra, but their fruits were significantly smaller. In addition, A. arguta var. giraldii (8x and 10x) had higher contents of nutrients such as ascorbic acid and amino acids; however, some important agronomic traits, including the content of total sugar and total acid, were significantly lower in the octaploids and decaploids. Moreover, octaploids and decaploids did not result in greater ecological adaptability for the challenging environments and climates. In conclusion, the differentiation of ecological adaptability and traits among natural kiwiberries’ cytotypes suggested that higher ploidy levels are not inevitably advantageous in plants. The findings of A. arguta and related taxa in geographical distribution and agronomic trait variations will facilitate their germplasm domestication.